Efeitos da insulinoterapia e superfícies hidrofílicas e superhidrofílicas na redução dos impactos do diabetes tipo I na osseointegração de implantes em ratos - Venâncio, Jessyca Figueira (2022)
Chronic hyperglycemia resulting from type I diabetes mellitus (DMTI) affects multiple organs, interfering with the quality of life of patients with the disease. In bone and, consequently, in the osseointegration of dental implants, this condition alters bone metabolism, compromising bone repair and biomechanical properties. Adjuvant therapies such as insulin therapy and changes in implant surfaces have been proposed to favor osseointegration and improve tissue conditions around implants. The general objective of this study was to evaluate the effect of insulin therapy and hydrophilic and superhydrophilic surfaces on the microarchitecture, biomechanics and osseointegration of implants in bones of rats with type I diabetes mellitus (DMTI). Analyzes by micro-computed tomography (MicroCT), biomechanical analysis, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used. The results showed that DMTI alters the microstructure, composition and hardness of the bone matrix, by reducing bone surface, cortical thickness, anisotropy, fractal dimension, collagen maturation and mineralization and bone microhardness. DMTI caused structural changes in bone tissue, affecting the osseointegration of implants, decreasing the process of bone neoformation. Insulin therapy minimized the effect of DMTI on cortical thickness and organic/mineral matrix in cortical bone in an experimental rat model. Insulin therapy showed favorable results for osseointegration, however, it did not normalize the repair, remaining significantly different from normoglycemic animals. Implants with a superhydrophilic surface favored osseointegration when associated with insulin therapy.